Mathematics Teacher’s Experience and Learning from the Perspective of Social Practice - Riscanevo Espitia, Lida Esperanza; Jiménez Espinosa, Alfonso (Universidad Pedagógica y Tecnológica de Colombia, 2017)
This reflection article presents a relation between experience and learning from the perspective of social practice, as a fundamental part in the mathematics teacher education. Such relation is shown through an extensive contextualization of different philosophical approaches on experience and their interpretations in the education area, with the aim of highlighting an emerging field of research that displays teacher learning in the process of creating a community of practice in order to live experiences and identify through them what is touching and transforming the mathematics teacher. In this way, the need to research on learning experience is underlined, not just to emphasize what the experience does not mean, but to recognize that the experience-learning relation is formative, given that the subject of learning is not only the subject of the experience but also the subject of formation.